Fetal lipidome and incident risk of food allergy: A prospective birth cohort study. Issue 2 (20th January 2022) - Hong, Xiumei; Liang, Liming; Ji, Hongkai; Frischmeyer‐Guerrerio, Pamela; Wang, Guoying; Pearson, Colleen; Stampfer, Meir; Hu, Frank B.; Wang, Xiaobin
Abstract: Background: Lipids are proposed to be important in developing adaptive immunity and allergy. However, studies to date reported inconsistent findings. Objective: To examine newborn lipidome (a comprehensive profiling of circulating lipid metabolites) on child's risk of developing food allergy (FA). The maternal‐cord joint effects of lipid metabolites on FA development were also investigated. Methods: This study included 647 mother‐child pairs from the Boston Birth Cohort and analyzed 202 lipid metabolites in cord plasma profiled by liquid chromatography tandem mass spectrometry. FA was defined based on standard clinical criteria. Logistic regression was applied to examine the relationships between individual metabolites and risk of FA. Results: Of the 647 children, 61 developed FA. Cord triacylglycerols of long carbon chains and multiple double bonds were significantly associated with decreased risk of FA. These associations were comparable across strata of pertinent maternal and child covariates, and were independent of maternal triacylglycerols when assessed simultaneously. Besides, cord and maternal triacylglycerols had an additive effect in association with risk of FA: Children having high (≥Median) C56:8 triacylglycerol levels in both cord and maternal plasma were at the lowest risk of developing FA (OR = 0.24, 95% CI = 0.10–0.56, p = .001), compared to those having low levels in both cord and maternal plasma. Conclusion: This is the first birth cohort study to link altered cord plasma lipidome with future risk of development FA during childhood. It calls for further investigation on triacylglycerols of long carbon chains and multiple double bonds as potential novel predictive biomarkers and therapeutic targets for FA.